Revalidation of elder's equation for accurate measurements of dispersion coefficients in natural flows (2014)
One of first practical definitions for numerical solutions of classical model of Advection-Dispersion was the Elder's equation developed in 1959. This relationship based on the theoretical guidance proposed by G.I. Taylor for long, straight pipes, extent successfully the method for the case of ideal prismatic, wide channels in open flow. However, wishing to apply it to real cases with varied geometry the results were not satisfactory due to several reasons which will be examined in this article. This limiting situation for the equation is inconvenient for two reasons: First, whatsoever it is a very used equation due to its simplicity and to the fact that involve geomorphologic parameters, without requiring tracers. Secondly but not the less important, because it is based on fundamental mechanisms that are widely accepted, and then they should not lead to results in conflict with experiments. For these reasons, and also because the study of water quality depends critically on the understanding of these processes, it is interesting to review this subject. It will be tried to show if it is used a longitudinal coefficient function of time it is possible to recover the applicability of equation. For this it is used an extended work of PhD thesis done by H.B. Fischer in the Mc Keck channel of Caltech on behavior of Elder's relationship.